Analisis Kesalahan Berbahasa dalam Pembentukan Kata pada Penulisan Teks Eksposisi Terhadap Siswa Kelas X MIPA 1 SMA Negeri 5 Wajo Kajian Morfologi - Ahmad Ghazali; Sutrisman; Nur Rahmi; Nurul Hidayah; Arisa Arisa (AIJER: Algazali International Journal Of Educational Research, 2021)
Abstract: Analysis of Language Errors in Word Formation in Exposition Text Writing for Class X MIPA 1 Students of SMA Negeri 5 Wajo Morphological Studies. This study aims to describe the form of language errors in writing exposition texts for class X MIPA 1 SMA Negeri 5 Wajo students using morphological studies. This type of research uses qualitative descriptive research methods. This researchwas carried out directly at SMA Negeri 5 Wajo to obtain qualitative description data. The object of this study is a language error in word formation in the writing of exposition texts for students of class X MIPA 1 SMA Negeri 5 Wajo: Morphological Studies. The technique of collecting the results of the analysis and discussion of this research can be found in the form of language errors in the field of morphology, namely errors in the process of forming the basic word into the word affix (duplication). A morphemic process that repeats the basic word form, either in whole, in part, or with changes in sound and (composition). Based on the results of the processed research data, it was found that language errors in affiliations were 26 words, errors were made in duplication, which was 3 words, and there were no language errors in composition. In addition to language errors at the morphological level, students also make language mistakes such as word writing errors and preposition writing errors. Keywords: Language Errors, Word Formation, Exposition Text